Local democracy denied? a personal journey into local government in Malaysia - Lim, Mah Hui (Strategic Information and Research Development Centre, 2020)
Local Democracy Denied? A Personal Journey Into Local Government In Malaysia. There are plenty of books on federal government and politics in Malaysia, but very few on local government. Yet it is the level of government that is closest to us and impacts our lives most directly and is the one least understood by the average person in the street. The author served as a councillor for six years on the Penang Island City Council, as a representative of civil society. It then provides a brief history of how local government in Malaysia evolved from the election to selection of local councillors, the structure of local government, its relationship with state governments and more - ending with a call to revive local democracy by strengthening public participation in local government.